Microbleeds may expand acutely after traumatic brain injury. (23rd March 2016) - Toth, Arnold; Kovacs, Noemi; Tamas, Viktoria; Kornyei, Balint; Nagy, Mate; Horvath, Andrea; Rostas, Tamas; Bogner, Peter; Janszky, Jozsef; Doczi, Tamas; Buki, Andras; Schwarcz, Attila
Graphical abstract: Highlights: A certain portion of the traumatic microbleeds changed within a week after the injury. This change occurred in forms of microbleed expansion and confluence. Due to this, both the overall microbleed count and volume was altered. Imaging timing may be relevant for optimizing the prognostic utility of this biomarker. Abstract: Background and purpose: Susceptibility weighted imaging (SWI) is a very sensitive tool for the detection of microbleeds in traumatic brain injury (TBI). The number and extent of such traumatic microbleeds (TMBs) have been shown to correlate with the severity of the injury and the clinical outcome. However, the acute dynamics of TMBs have not been revealed so far. Since TBI is known to constitute dynamic pathological processes, we hypothesized that TMBs are not constant in their appearance, but may progress acutely after injury. Materials and methods: We present here five closed moderate/severe (Glasgow coma scale ≤ 13) TBI patients who underwent SWI very early (average = 23.4 h), and once again a week (average = 185.8 h) after the injury. The TMBs were mapped at both time points by a conventional radiological approach and their numbers and volumes were measured with manual tracing tools by two observers. TMB counts and extents were compared between time points. Results: TMBs were detected in four patients, three of them displaying an apparent TMB change. In these patients, TMB confluence and apparent growth were detected in the corpus callosum, coronal radiation or subcortical white matter, while unchanged TMBs were also present. These changes caused a decrease in the TMB count associated with an increase in the overall TMB volume over time. Conclusion: We have found a compelling evidence that diffuse axonal injury-related microbleed development is not limited strictly to the moment of injury: the TMBs might expand in the acute phase of TBI. The timing of SWI acquisition may be relevant for optimizing the prognostic utility of this imaging biomarker.